Oculo-auriculo-vertebral Spectrum (Goldenhar Syndrome): Presentation of Three Cases - Benli, Samet; Caglar, Atika; Taskin, Erdal; Aydin, Mustafa (Mashhad Univ Med Sciences, 2021)
Background: The oculo-auriculo-vertebral spectrum (OAVS) includes three closely related rare congenital diseases of different severity with an incidence of 1/3500-7000 individuals. The involvement is usually unilateral; however, bilateral involvement may also occur. In addition to craniofacial anomalies, defects in the cardiovascular, genitourinary, vertebral, and central nervous systems can be observed as well. The phenotype of the cases is highly variable. Goldenhar syndrome is the most severe form of this condition. Case report: In total, three instructive cases of Goldenhar syndrome with different features have been reported in the present case study. The most common ear anomalies among these three cases included external auditory canal atresia, helix deformities, preauricular skin tag and/or ear pitting, microtia, and conductive hearing loss. The second case was presented with hemifacial microsomia on the more severely affected right side, and the third case had bilateral Brushfield spots and a dermolipoma ophthalmological findings. Conclusion: Based on the findings of the present study, OAVS should also be considered in the differential diagnosis of the cases with facial and ear anomalies.
Keywords: Congenital anomaly; Goldenhar syndrome; Hemifacial microsomia; Oculo-auriculo-vertebral disorder